2004
DOI: 10.1214/009053604000000490
|View full text |Cite
|
Sign up to set email alerts
|

Convergence rates for posterior distributions and adaptive estimation

Abstract: The goal of this paper is to provide theorems on convergence rates of posterior distributions that can be applied to obtain good convergence rates in the context of density estimation as well as regression. We show how to choose priors so that the posterior distributions converge at the optimal rate without prior knowledge of the degree of smoothness of the density function or the regression function to be estimated.Comment: Published by the Institute of Mathematical Statistics (http://www.imstat.org) in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 16 publications
(27 reference statements)
0
42
0
Order By: Relevance
“…Posterior convergence rates were studied in Ghosal et al (2000) and Shen and Wasserman (2001). Belitser and Ghosal (2003), Ghosal et al (2003), Huang (2004) the theorem implies asymptotic equivalence between standard confidence and credible sets. Chernozhukov and Hong (2003) and Kleijn and van der Vaart (2012) prove Bernstein-von Mises type theorems for misspecified parametric models, 2 and Panov and Spokoiny (2013) consider settings with increasing dimension of the nuisance parameter.…”
Section: Semiparametric Bernstein-von Mises Theoremmentioning
confidence: 96%
“…Posterior convergence rates were studied in Ghosal et al (2000) and Shen and Wasserman (2001). Belitser and Ghosal (2003), Ghosal et al (2003), Huang (2004) the theorem implies asymptotic equivalence between standard confidence and credible sets. Chernozhukov and Hong (2003) and Kleijn and van der Vaart (2012) prove Bernstein-von Mises type theorems for misspecified parametric models, 2 and Panov and Spokoiny (2013) consider settings with increasing dimension of the nuisance parameter.…”
Section: Semiparametric Bernstein-von Mises Theoremmentioning
confidence: 96%
“…Belitser and Ghosal (2003) showed that the strategy works for an infinite-dimensional normal. Ghosal et al (2003) and Huang (2004) obtained similar results for the density estimation problem. Kleijn and van der Vaart (2002) considered the issue of misspecification, where p 0 may not lie in the support of the prior.…”
Section: Theorem 1 Let θ = M(z + ) With the Total Variation Distancementioning
confidence: 62%
“…For these purposes, we consider only the case in which the support of the prior distribution contains only uniformly bounded regression functions as stated in the Assumption P.3 below. Similar assumptions about the uniform boundedness of regression function can be found in Shen and Wasserman (2001) and Huang (2004). In this case, the probability distribution of Q is assumed to be known.…”
Section: Assumption P2 Definementioning
confidence: 92%
“…Posterior consistency and the question about the rate of convergence of posterior distribution in nonparametric regression problems have been mainly studied under Gaussian noise distribution (e.g. Shen and Wasserman 2001;Huang 2004;Choi and Schervish 2007) and further efforts are expected to be taken under the general noise distribution.…”
Section: Introductionmentioning
confidence: 99%